Commodity modeling and pricing : methods for analyzing resource market behavior - Schaeffer, Peter V. (Wiley, 2008)
An industry leader reveals how to effectively analyze, model, and forecast today's commodity markets. Commodity Modeling and Pricing provides extensions and applications of state-of-the-art methods for analyzing resource commodity behavior. Applicatio.